Upaya Meningkatkan Pemahaman Siswa dalam Pemilihan Karir Menggunakan Layanan Informasi - Qurbi, Abdullah; Diswantika, Noviana; Violetha, Marcella Putri (STKIP PGRI Bandar Lampung, 2020)
This article focuses on guidance and counseling teachers attempt to increase students' understanding of career choice plans by using information because there is still a low level of career choice plans for the future, so information services are needed to increase students' understanding. about career choice plans. This writing method is a literature study (review). The data and information obtained comes from various reading sources and is compiled based on the results of studies from the data and information obtained. The data analysis technique is descriptive argumentative. Writing is done by looking at the relationship and synchronization between one data and information and other data and information according to the topic being studied. Then conclusions are drawn from the written work.Based on data discussion, it can be concluded that the efforts of guidance and counseling teachers to increase students' understanding of planning career choices by using information services can help students with knowledge about themselves and the world of work so that students are able to plan and make the right decisions. for his future career.